The Transfiguration of Jesus and the Easter Visions - Guijarro Oporto, Santiago (Biblical theology bulletin, 2017)
John Pilch was a forerunner in the study of extraordinary experiences in the New Testament. As a token of gratitude, this paper is devoted to him. It focuses on the Transfiguration story, and suggests that Jesus may have initiated his disciples to access alternate states of consciousness by means of visions they may have learned to re-enact. This pre-Easter practice would explain why the encounter with the Risen Lord took place primarily through visions whose basic pattern is that of the vision reported in this episode.